Characterization of serine hydroxymethyltransferase GlyA as a potential source of D-alanine in Chlamydia pneumoniae - De Benedetti, Stefania; Bühl, Henrike; Gaballah, Ahmed; Klöckner, Anna; Otten, Christian; Schneider, Tanja; Sahl, Hans-Georg; Henrichfreise, Beate (Frontiers in Cellular and Infection Microbiology, 2014)
For intracellular Chlamydiaceae, there is no need to withstand osmotic challenges, and a functional cell wall has not been detected in these pathogens so far. Nevertheless, penicillin inhibits cell division in Chlamydiaceae resulting in enlarged aberrant bodies, a phenomenon known as chlamydial anomaly. D-alanine is a unique and essential component in the biosynthesis of bacterial cell walls. In free-living bacteria like Escherichia coli, penicillin-binding proteins such as monofunctional transpeptidases PBP2 and PBP3, the putative targets of penicillin in Chlamydiaceae, cross-link adjacent peptidoglycan strands via meso-diaminopimelic acid and D-Ala-D-Ala moieties of pentapeptide side chains. In the absence of genes coding for alanine racemase Alr and DadX homologs, the source of D-Ala and thus the presence of substrates for PBP2 and PBP3 activity in Chlamydiaceae has puzzled researchers for years. Interestingly, Chlamydiaceae genomes encode GlyA, a serine hydroxymethyltransferase that has been shown to exhibit slow racemization of D- and L- alanine as a side reaction in E. coli. We show that GlyA from Chlamydia pneumoniae can serve as a source of D-Ala. GlyA partially reversed the D-Ala auxotrophic phenotype of an E. coli racemase double mutant. Moreover, purified chlamydial GlyA had racemase activity on L-Ala in vitro and was inhibited by D-cycloserine, identifying GlyA, besides D-Ala ligase MurC/Ddl, as an additional target of this competitive inhibitor in Chlamydiaceae. Proof of D-Ala biosynthesis in Chlamydiaceae helps to clarify the structure of cell wall precursor lipid II and the role of chlamydial penicillin-binding proteins in the development of non-dividing aberrant chlamydial bodies and persistence in the presence of penicillin.